Boosting India's milk production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Inexpensive nutrient blocks have been developed for tethered buffaloes and cattle as a way to increase milk production in India. Enthusiastic farmers have dubbed them 'buffalo chocolate'. Nutrient or urea/molasses blocks are not new, but these have...